2018
DOI: 10.1111/sms.13230
|View full text |Cite
|
Sign up to set email alerts
|

Non‐uniformity in pre‐insertional Achilles tendon is not influenced by changing knee angle during isometric contractions

Abstract: Achilles tendinopathy remains a prevalent condition among recreational and high-level athletes. Mechanical loading has become the gold standard in managing these injuries, but exercises are often generic and prescribed in a "one-size-fits-all" principle. The aim of this study was to evaluate the impact of knee angle changes and different levels of force production on the non-uniform behavior in the Achilles tendon during isometric contractions. It was hypothesized that a flexed knee position would lead to a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…4). This is in contrast with several studies in human subjects in which no significant effects of knee angle on non-uniform displacements within the human AT were reported (Bogaerts et al, 2018;Stenroth et al, 2019). This may be explained by differences in the location along the AT for which local deformations were assessed, being more proximal in our study compared to most studies in humans.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…4). This is in contrast with several studies in human subjects in which no significant effects of knee angle on non-uniform displacements within the human AT were reported (Bogaerts et al, 2018;Stenroth et al, 2019). This may be explained by differences in the location along the AT for which local deformations were assessed, being more proximal in our study compared to most studies in humans.…”
Section: Discussioncontrasting
confidence: 99%
“…In our previous study, we investigated effects of differential muscle activation on subtendon deformations, but kept the position of the knee and ankle joints constant (Finni et al, 2018). In humans, several previous studies involving both passive and active muscle conditions reported no effects of knee joint angle on non-uniformities in the displacement within the AT (Bogaerts et al, 2018;Stenroth et al, 2019). Effects of knee angle on strains within the various subtendons of the AT have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, however, the non‐uniform behavior is present in both exercises (DF and N) and appears not to be influenced by the degree of dorsiflexion. More specific, there is always significantly more local tissue displacement in the middle layer compared with the superficial layer, the deep compared with the middle layer, and the deep compared with the superficial layer 15 . Therefore, the differential impact of DF vs N loading seems to impact the intratendinous shear strain, which is thought to be linked with etiology of tendinopathy, in a similar way during both exercises 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Healthy participants were recruited from a group of coworkers at the department of Physical and Rehabilitation Medicine of the University Hospitals Leuven. This cohort was the same as for another study, 15 where the role of changing knee angle on intratendinous behavior during Achilles loading exercises was evaluated. Subjects with previous history of Achilles tendinopathy, rupture, surgery, and/or systemic or neuromuscular diseases were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Recent human studies have demonstrated non-uniform displacements in the AT, revealing that the anterior portion of the AT experiences greater displacements than the posterior portion during passive ankle motions (Arndt et al, 2012), eccentric plantarflexor contractions (Slane and Thelen, 2014), and isometric contractions, irrespective of the knee angle or level of force produced (Bogaerts et al, 2018). While these studies in human subjects were not able to attribute the non-uniform behavior to specific sub-tendons, recent work has shown that the SOL sub-tendon in the rat AT experiences significantly different displacements and strains than the lateral GAS sub-tendon during isometric contractions (Finni et al, 2018;Maas et al, 2020), indicating non-uniform deformations of the AT sub-tendons.…”
Section: Introductionmentioning
confidence: 99%